Impacts of the Rise of Subsidized Diesel Fuel Price to the Commodity Price Through the Perspective of Islamic Economy - Nugroho, Anton Piyo; Tulasmi, (LAA MAISYIR : Jurnal Ekonomi Islam, 2023)
Some of the opinions of classical fuqoha' such as Ibn Khaldun, Ibn Taimiyah, Abu Yusuf, and so on stated that price fixing is only done through the number of requests and offers. However, along with the times, some fuqoha' argue that price fixing by the government may be done for the benefit of all Indonesian people. On September 3, 2022 the Government of the Republic of Indonesia raised the price of subsidized fuel for the Pertalite type from Rp. 7,650/liter to Rp. 10,000/liter. Then the type of Solar Price from the price of Rp. 5,150/liter to Rp. 6,800/liter. The increase in fuel prices can have direct and indirect implications for commodity prices. To ensure this, this study aims to analyze the long-term and short-term effects of the increase in the price of subsidized diesel fuel using the VAR/VECM model using E-Views 10.